(untitled) (Medical Forum Monthly, 2024)
Objectives: To review the clinical presentations, management and outcomes of heat stroke patients presented to Hamdard University Hospital, Karachi in summer 2015. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Hamdard University Hospital (Taj Medical Complex), Karachi from 15th to 30th June 2015. Methods: A retrospective analysis of database of 51 patients presented with high grade fever (>1040F) and altered sensorium was performed. All data were transferred to proforma which included patient’s demographic features (name, age and sex), clinical and laboratory parameters, treatment given, duration of hospital stay, outcomes (death or alive) and reasons of mortality. The SPSS version 19 was used for statistical analyses. Results: Majority of the patients (63%) were between 61-80 years of age group with mean+SD age was 69.24+11.28 years. Males were affected more than females (60.7% vs. 39.3% respectively). Out of 51, 41 (80.4%) had co-morbidities and were on regular medications. The mean+SD Glasgow Coma Scale at the time of presentation was 10.29+4.33. The major laboratory derangements were hyponatremia (68.6%), elevated blood urea (52.9%), serum creatinine (41.2%) and alanine transferase (15.6%). Standard treatment strategies were provided to all patients. Out of 51, 19 (37.3%) patients were expired as a result of multi-organ failure, shock, arrhythmias and rhabdomyolysis. Conclusion: Heat stroke is common in older males especially those who had co-morbidities. It carries a significant mortality due to multiorgan failure and shock.